Pengaruh Produk, Harga Dan Distribusi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pengguna Handphone Merek Vivo Studi Kasus Pada Mahasiswa FEB Universitas Muhammadiyah Metro - Fuadi, Selamet; Suwarto, Suwarto; Widyani, Eka (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study is to determine the effect of products, prices, and distribution oncustomer loyalty both directly or indirectly through customer satisfaction. Research methodsrequire quantitative research. Objects in research are products, prices, distribution, loyalty,and customer satisfaction with Vivo brand cellphone users. The population in the study wereFEB students of Muhammadiyah Metro University. The sample in the study was taken usingthe random sampling technique with the amount of sampling determined by the Slovinmethod. The number of samples produced is 91 respondents. The instrument in this studyused a questionnaire. Data analysis in this study uses path analysis. The results showed thatproducts directly affect customer loyalty, prices directly affect customer loyalty, distributiondirectly affects customer loyalty. Products, prices, and distributions have an indirect effect oncustomer loyalty, namely through customer satisfaction.